Physical Properties of Polyvinyl Alcohol/Chitosan Films with the Addition of Anthocyanin Extract from Butterfly Pea for Food Packaging Applications - Siti Khanifah; Alda Dwi Karina Legowo; Sholihun Sholihun; Ari Dwi Nugraheni (Indonesian Journal of Chemistry, 2023)
Composites of polyvinyl alcohol (PVA) and chitosan (CH) polymers, with the addition of anthocyanin (AN) obtained from the butterfly pea flower, were prepared using drop-casting. The composites were made by adding different concentrations of 5–40% anthocyanin with 5 wt.% PVA and 2 wt.% CH solutions (weight ratio of PVA/CH is 80:20). These polymers solution was mixed at 80 °C and dried using the drop-casting method at 25 °C for 48 h. The composites were characterized using a scanning electron microscope (SEM), Fourier-transform infrared (FTIR), ultraviolet-visible (UV–vis spectroscopy), contact angle, antibacterial properties, and food packaging applications. The morphology obtained using an SEM showed that the PVA/CH surface with AN and glycerol was smoother than that of PVA/CH. The increased absorption at a wavelength of 650–700 nm from UV-vis spectroscopy confirmed the success addition of AN. The contact angles of PVA/CH/AN and PVA/CH/GS/AN films were 15°–66°, which showed that the films were hydrophilic. The simple antibacterial test with Escherichia coli and Staphylococcus aureus showed 16 mm inhibition zone by adding AN. The test results of these characteristics show the potential for using PVA/CH/AN and PVA/CH/GS/AN composite film to be used as an excellent development food packaging material.